Pemanfaatan Ecobrick sebagai Solusi Pengelolaan Sampah Plastik di Nagari Langki - Zulfa, Aisyah Mag'ribi; Heriansyah, Syella Avriani; Rahmawati, Lili; Ramadhani, Diva; Putri, Tita Septiani; Sari, Desi Purnama (Universitas Negeri Padang, 2025)
Plastic waste management in Nagari Langki, Tanjung Gadang Subdistrict, Sijunjung District is still suboptimal due to low public awareness of sorting and managing household waste. This study aims to implement the use of ecobricks as a community-empowered solution for plastic waste management. The method used is participatory-educational, involving the community through socialization, education, training, and ecobrick-making practices. The activities were conducted at SDN 03 Langki, SDN 25 Langki, SMPN 31 Sijunjung, and the Village Office in June 2024. The results of the activities showed high enthusiasm among the community, particularly housewives and students, in collecting and processing plastic waste into ecobricks. The program produced approximately 50 ecobrick bottles, which were assembled into two units of chairs and donated to PAUD Parmato Bundo and TK Harapan Bunda. The use of ecobricks has proven effective in increasing community awareness and participation in plastic waste management. This program has the potential to be developed as a sustainable community-based waste management model.